Double embedded rings of a digit leading to amputation - Liew, Siew Khei; Teck, Siong Fong; Kok, Kheng Teh (World Scientific Publishing, 2021)
Chronic embedded-ring injury is a rare and uncommon presentation. This is also known as "chronic ring erosion" or "embedded ring syndrome" in the literature. Injury of this type has been associated with psychological impairment causing neglect of such injury. We herein describe a case of double embedded rings on the right ring finger in a 30-year-old healthy construction worker. A primary amputation at the metacarpophalangeal joint was performed in view of the chronicity of his condition and associated neurovascular damage. Early removal of ring is of paramount importance in any ring-associated injuries. However, fear of losing a digit has been the reason of delay in seeking medical treatment, which in turn ended up in dire consequences.